The Framework of Socio-Religious Harmony in Sabah, East Malaysia: An Application of Fuzzy Delphi Method - Mohd Nazmi Mohd Khalli; Suraya Sintang; Assis Kamu (Elsevier, 2022)
The reality of socio-religious harmony in Sabah is undeniable. Some visible evidence, and its distinct social environment foster religious tolerance and encouraging people to accept others as they are. On what grounds does this harmony persist, given that situations in Malaysia show that interfaith disputes have never been silent? Examining this phenomenon considers the community, even attempting to disrupt Sabah's long-established harmonious relations. Therefore, the study goal is to develop a framework of socio-religious harmony in Sabah which is unique in its own diverse culture and religions. This study employs the Fuzzy Delphi Method (FDM), prioritizing expert consensus in determining the investigation results. The study has selected seventeen experts from various professional backgrounds: academicians, policymakers, community leaders, non-government (NGO), and religious leaders. The results have identified three constructs, nine elements, and 43 of the 62 expert-agreed-upon criteria, which were then displayed hierarchically as a model of socio-religious harmony framework in Sabah. The finding also reveals the top ten highest ranking criteria agreed upon by experts for considering variables of establishing socio-religious harmony in Sabah. Ultimately, the study gives a clear framework for future studies to measure a level of social harmony in Sabah, and significantly contribute as a guideline throughout Malaysia as a whole.